Towards Effective Cryptocurrency Taxation: Comparative Policy Lessons from the EU, the United States, and Southeast Asia - Azizbek Mansurov (PT Advanced business journal, 2026)
Rapid expansion within cryptocurrency markets has presented global tax authorities with significant hurdles, specifically regarding the determination of ownership, valuation methodologies, and jurisdictional liability for digital assets. Disparate taxation policies among leading economies have resulted in persistent inconsistencies concerning regulatory compliance, enforcement protocols, and fiscal equity. This research performs a comprehensive comparative analysis of cryptocurrency taxation frameworks across the European Union (EU), the United States (US), and Southeast Asia, with a focused lens on legal classifications, regulatory structures, and fiscal consequences. Qualitative comparative methodology serves as the foundation for this study, integrating policy document evaluations, case law reviews, and the synthesis of secondary data from official governmental and institutional archives. Findings indicate that the European Union emphasizes regional harmonization through the Markets in Crypto-Assets (MiCA) regulation, whereas the United States maintains a capital gains taxation model predicated on specific asset categorizations. Southeast Asian nations, conversely, demonstrate fragmented and evolving strategies that are heavily influenced by varying levels of institutional maturity. Analysis suggests that successful cryptocurrency taxation remains contingent upon high levels of transparency, robust interagency coordination, and advanced digital infrastructure readiness. Global policy coherence appears essential for mitigating tax arbitrage and fostering equitable fiscal governance within the modern digital economy. These conclusions offer a valuable contribution toward establishing a unified conceptual framework for the management of cross-border digital asset taxation.